Effects of Tetrabasic Zinc Chloride on Growth Performance, Nutrient Digestibility and Fecal Microbial Community in Weaned Piglets - Zhang, Gang; Hu, Guoqing; Yang, Zhenyan; Zhao, Jinbiao (Frontiers in Veterinary Science, 2022)
The study was conducted to explore the effects of tetrabasic zinc chloride (TBZC), as an alternative to zinc oxide (ZnO), on growth performance, serum indexes, and fecal microbiota of weaned piglets. A total of 108 weaned piglets (average initial body weight of 7.84 ± 0.97 kg) were randomly allocated into one of three dietary treatments with six replicate pens and six piglets per pen. The dietary treatments included a control diet (CON, negative control), a ZnO diet (CON + 1,600 mg Zn/kg from ZnO, positive control), and a TBZC diet (CON + 1,000 mg Zn/kg from TBZC). The average daily gain of pigs in the TBZC group was greater (P < 0.05) than those in CON and ZnO groups during the whole period. Piglets fed the ZnO and TBZC diets showed lower (P < 0.05) diarrhea incidence than those fed the CON diet during d 1-14 and the whole period. Piglets fed the TBZC diet had higher (P < 0.05) digestibility of crude protein and gross energy than those fed the CON diet. Serum concentrations of IGF-I and GH, as well as ALP activity, were significantly elevated (P < 0.05) in the TBZC treatment group compared to the CON group on d 14. Piglets fed the ZnO diet had greater (P < 0.05) acetate and total short-chain fatty acids concentrations, while the TBZC diet had greater (P < 0.05) fecal acetate and propionate concentrations on d 28. Moreover, TBZC supplementation significantly increased (P < 0.05) microbial α-diversity compared with the CON group. The fecal microbiota of piglets in ZnO and TBZC treatment groups tended (P = 0.08) to have greater relative abundance of Prevotellaceae compared with the CON piglets. In conclusion, TBZC acted as a suitable alternative to ZnO to reduce zinc excretion, and improve growth performance of weaned piglets.